Fetal Heart Function by Tricuspid Annular Plane Systolic Excursion and Ventricular Shortening Fraction Using STIC M-Mode: Reference Ranges and Validation - Tedesco, Giselle Darahem; de Souza Bezerra, Marilim; Barros, Fernanda Silveira Bello; Martins, Wellington P.; Nardozza, Luciano Marcondes Machado; Mattar, Rosiane; Moron, Antonio Fernandes; Rolo, Liliam Cristine; Araujo Júnior, Edward (American Journal of Perinatology, 2017)
Objective To determine the reference values for fetal tricuspid annular plane systolic excursion (f-TAPSE) and fetal ventricular shortening fraction (f-VSF) using spatiotemporal image correlation (STIC) with M-mode, and validate these curves in fetuses of pregnant women with preexisting diabetes mellitus (DM) and with intrauterine growth restriction (IUGR). Study Design Crosssectional study assessed 300 fetal cardiac volumes of normal pregnancies between 20 and 33 + 6 weeks of gestation. For the construction of the reference curves, we used a polynomial regression model adjusted with the coefficient of determination (R2). For the calculation of reproducibility, the concordance correlation coefficient (CCC) was used.Results f-TAPSE value correlated with gestational age (GA, R2 = 0.46), whereas fetal right ventricular shortening fraction (f-RVSF, R2 = 0.02) and fetal left ventricular shortening fraction (f-LVSF, R2 = 0.005) did not vary with GA. Fetuses of pregnant women with preexisting DM (30) had lower values of f-RVSF (p = 0.028), f-LVSF (p = 0.001), and f-TAPSE (p = 0.009) than normal fetuses. The f-TAPSE values were lower (p = 0.005) in IUGR group (17). The f-TASPSE values showed adequate reliability as well as good intra and interobserver concordance (CCC = 0.95 and 0.79, respectively). Conclusion The reference ranges for f-TAPSE, f-RVSF, and f-LVSF using the STIC M-mode were established and had good reproducibility for f-TAPSE measurements.
Keywords: reference ranges; fetal heart function; tricuspid annular plane systolic excursion; ventricular shortening fraction; M-mode; three-dimensional ultrasound